Effects of community and center-based settings on the alertness of persons with profound mental retardation. - Belfiore, P J (1993)
We studied effects of different settings on the behavior of persons with profound mental retardation. Adaptive (alert) and nonadaptive behaviors were observed in two community settings and a center setting. Results of the descriptive assessment showed that participants engaged in a higher percentage of adaptive behaviors and a lower percentage of nonadaptive behaviors in the "high stimulation" community setting. The results are discussed in light of environmental setting events on persons with profound mental retardation.